PENGARUH INDUSTRI, TENAGA KERJA INDUSTRI DAN PDRB SEKTOR INDUSTRI TERHADAP DISPARITAS PENDAPATAN ANTAR WILAYAH PROVINSI JAWA TIMUR - Nurul Fadilah; Ida Nuraini; Dwi Susilowati (Program Studi Ekonomi Pembangunan, 2017)
This study aims to see the difference and the magnitude of income disparity between regions in East Java Province, and to determine the effect of industry, labor industry and industry sector PDRB to income disparity between regions in the province of East Java in 2012-2015. This research uses quantitative approach with the type of data structure that is panel data consisting of 29 regencies and 9 cities of East Java Province in 2012-2015. Analyzer used is multiple linear regression analysis and williamsom index. From result of analysis got result that only PDRB industrial sector which have significant effect to income disparity with positive direction while industry and labor industry have not significant effect. So it can be concluded that industrialization in East Java Province has not been able to resolve the income disparit y between regions in East Java Province in 2012-2015.Keywords: income disparity, industrialization, PDRB